Дискретний метод оптимізації календарного планування поліграфічного підприємства - Король, А. Л. (ТОВ «Видавництво Ліра-К», 2025)
This work is devoted to the inverse problem of calendar planning of the technological process at a printing enterprise and the procedure for reducing this problem to the standard form of a discrete programming problem.
Keywords: оптимізація календарного планування; поліграфічне підприємство